Method to Calculate Working Surface Abutment Pressure Based on Key Strata Theory. (15th July 2019) - Han, Hongkai; Xu, Jialin; Wang, Xiaozhen; Xie, Jianlin; Xing, Yantuan
Abstract : Overburden key strata (KS) have a significant influence on abutment pressure distribution. However, current calculation methods for working surface abutment pressure do not consider the influence of the overburden KS. This study uses KS theory to analyze the overburden load transferred to coal-rock masses on both sides of the stope through fractured blocks in different layers of the KS in the fissure zone and KS in different layers of the curve subsidence zone. Using Winkler's elastic foundation beam theory, we consider the fissure zone KS on the coal mass side and the curve subsidence zone KS as many elastic foundation beams interact with each other. A method to calculate the abutment pressure of the coal mass and the goaf was then established, considering the influence of the overburden KS. The abutment pressure distribution of working surface 207 after mining was then calculated using our method, based on mining conditions present in the Tingnan coal mine. The calculated results were verified using measurements from borehole stress meters and microseismic monitoring systems, as well as numerical simulations. In addition, the calculation results were used to determine a reasonable position for the stopping line and remaining width of the roadway's protection coal pillar in working surface 207. The results of this study can be used to calculate the abutment pressure distribution of the working surface under a variety of overburden KS conditions. The results can also provide guidance for forecasting and preventing mine dynamic hazards, controlling the surrounding rock in mining roadways, determining reasonable widths for protection coal pillars, and designing the layout of mining roadways.